Overview of Sense Of Community in Administrative Section Employees at Muhammadiyah University of Sidoarjo - Effy Wardati Maryam (Psikologia : Jurnal Psikologi, 2017)
This study aims to determine the description of a sense of community in the administrative employees at the Universitas Muhammadiyah Sidoarjo. Subjects in this study were employees of the administration in UMSIDA, amounting to 51 person, with the technique of determining the sample using saturated sampling. The data collection tool uses a sense of community scale by adapting 24 items of Sense of Community Index Version Two (SCI-2) which refers to the sense of community theory proposed by McMillan and Chavis. Data analysis techniques in this study using descriptive statistical techniques. The results of data analysis show that the sense of community in the administrative staff at Muhammadiyah University of Sidoarjo generally are in the medium category. Whereas if viewed from the existing dimensions, shared emotional connection dimension get the highest score compared with other dimensions.